Strengthening Postpartum Education Through Kegel Exercise Pocket Books and Educational Videos - Lolowang, Nolla Lisa; Elizabeth Ancient (Jurnal Pengabdian Masyarakat Jurusan Keperawatan, 2023)
Sexual self-efficacy is an individual's perception of his or her ability to refuse sex or engage in safe sex practices in social situations where sexual intercourse is likely. Vaginal delivery causes pressure on the vaginal floor which affects the strength and endurance of the pelvic floor muscles. This can result in decreased sexual arousal function and lead to poor orgasms. The strategy to increase sexual self-efficacy in women during postpartum is through Kegel exercises. Kegel exercises are very efficient in increasing pelvic floor muscle strength. The stages of implementation are situation analysis, problem identification, community service plans, and implementation of educational activities. The method of activity carried out is the method of brainstorming and dissemination with the use of guidebooks and educational videos. This activity increases the knowledge of health workers about Kegel exercises from 10 questions the average score is 14.72 correct (98.13%). After the participants received material and socialization about Kegel exercises through pocketbooks and educational videos, the results obtained from the 15 questions on average increased by 15 correct (100%). This shows that the socialization of Kegel exercises through pocketbooks and educational videos has a positive impact, and is beneficial for health workers in providing counseling to cadres and postpartum mothers in their target areas.